S07-3: Holistic Promotion of Physical Activity Based on Physical Literacy: Results and Implications of the PLACE Intervention (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Although the concept of physical literacy (PL) combines physical, cognitive, and affective aspects into a holistic perspective for promoting active lifestyles and has gained increasing importance internationally, PL-based interventions and practical findings are still in their infancy in Germany. The goal of the present study was to evaluate the main phase of an extracurricular PL intervention (PLACE study) to promote health-enhancing physical activity in eight to ten-year-old children in different districts of Bremen, Germany (Pöppel et al., 2024).Methods: We used an explanatory sequential mixed-methods design, built on five core dimensions derived from the inter-/national discussion on criteria for quality experiences in students (e.g. Ní Chróinín et al., 2018), which were assessed by comparing the intervention with regular physical education (PE). In group interviews with 40 children, we started with nonverbal reactions to quantitatively assess individual judgements along the five criteria, followed by qualitative statements to elicit verbal explanations to children’s decisions. The collected data were analysed using binomial tests and supplemented with qualitative findings.Results: The children reported no differences between the PL intervention and compulsory PE for the dimensions ‘social interaction’, ‘improvement of motor skills’, and ‘teaching and classroom management’ (z ≤ 1.67, p ≥. 095). However, the PL intervention was superior in the dimensions ‘cognitive activation’ (z = 3.68, p